Initial studies on brace-type shear fuses. (1st April 2020) - Jia, Liang-Jiu; Xie, Jiang-Yue; Wang, Zeqing; Kondo, Kana; Ge, Hanbin
Highlights: A new type of high-performance brace-type shear fuses (termed as BSF) is proposed. The cover plates were perforated making damage of the core plate detectable. Experimental study on effects of critical design parameters is conducted. Excellent cumulative ductility was verified by the experimental results of the proposed BSFs. Abstract: This paper proposes new brace-type shear fuses (BSFs) connected in series. The BSF consists of a core plate, two filling plates, two perforated cover plates, unbonding material and bolts. It is designed to dissipate seismic energy via yielding mainly under shear. Perforated cover plates make damage of the core plate visible. To analyze BSFs, seven specimens were designed with different number of shear fuses, tension-to-shear strength ratios and radii of shear fuses. In the experiments, it was found that the deformation capacity had positive correlation with number of shear fuses, tension-to-shear strength ratio, and radii of shear fuses. No buckling of the core plates occurred due to the short length of specimen. Fracture modes of all the specimens were shear rupture. Contact between the lateral sides of core plate and filling plates due to flexural deformation was observed, which led to significant increase of force in both tension and compression. In addition, initial stiffness and yield force of BSFs were derived based on the Principle of Virtual Work. A design criterion to avoid direct contact was also proposed for design of BSFs.